Targeting SAMHD1 with hydroxyurea in first‐line cytarabine‐based therapy of newly diagnosed acute myeloid leukaemia: Results from the HEAT‐AML trial. (18th August 2022) - Jädersten, Martin; Lilienthal, Ingrid; Tsesmetzis, Nikolaos; Lourda, Magda; Bengtzén, Sofia; Bohlin, Anna; Arnroth, Cornelia; Erkers, Tom; Seashore‐Ludlow, Brinton; Giraud, Géraldine; Barkhordar, Giti S.; Tao, Sijia; et al.
Abstract: Background: Treatment of newly diagnosed acute myeloid leukaemia (AML) is based on combination chemotherapy with cytarabine (ara‐C) and anthracyclines. Five‐year overall survival is below 30%, which has partly been attributed to cytarabine resistance. Preclinical data suggest that the addition of hydroxyurea potentiates cytarabine efficacy by increasing ara‐C triphosphate (ara‐CTP) levels through targeted inhibition of SAMHD1. Objectives: In this phase 1 trial, we evaluated the feasibility, safety and efficacy of the addition of hydroxyurea to standard chemotherapy with cytarabine/daunorubicin in newly diagnosed AML patients. Methods: Nine patients were enrolled and received at least two courses of ara‐C (1 g/m 2 /2 h b.i.d. d1‐5, i.e., a total of 10 g/m 2 per course), hydroxyurea (1–2 g d1‐5) and daunorubicin (60 mg/m 2 d1‐3). The primary endpoint was safety; secondary endpoints were complete remission rate and measurable residual disease (MRD). Additionally, pharmacokinetic studies of ara‐CTP and ex vivo drug sensitivity assays were performed. Results: The most common grade 3‐4 toxicity was febrile neutropenia (100%). No unexpected toxicities were observed. Pharmacokinetic analyses showed a significant increase in median ara‐CTP levels (1.5‐fold; p  = 0.04) in patients receiving doses of 1 g hydroxyurea. Ex vivo, diagnostic leukaemic bone marrow blasts from study patients were significantly sensitised to ara‐C by a median factor of 2.1 ( p  = 0.0047). All nine patients (100%) achieved complete remission, and all eight (100%) with validated MRD measurements (flow cytometry or real‐time quantitative polymerase chain reaction [RT‐qPCR]) had an MRD level <0.1% after two cycles of chemotherapy. Treatment was well‐tolerated, and median time to neutrophil recovery >1.0 × 10 9 /L and to platelet recovery >50 × 10 9 /L after the start of cycle 1 was 19 days and 22 days, respectively. Six of nine patients underwent allogeneic haematopoietic stem‐cell transplantation (allo‐HSCT). With a median follow‐up of 18.0 (range 14.9–20.5) months, one patient with adverse risk not fit for HSCT experienced a relapse after 11.9 months but is now in second complete remission. Conclusion: Targeted inhibition of SAMHD1 by the addition of hydroxyurea to conventional AML therapy is safe and appears efficacious within the limitations of the small phase 1 patient cohort. These results need to be corroborated in a larger study. Abstract :